Monitoring and Notification System for Hot Press Machine Operation with Internet of Things Technology - Kuankhonsan, Wiyossapon; Wattana, Buncha (Frontiers in Engineering Innovation Research, 2022)
This research paper presents a system for monitoring and notifying to prevent damages caused by an abnormal operation of the hot press machine with Internet of Things technology. The current and voltage values supplied to the heater of the hot press machine are monitored by sensors in normal and abnormal operating conditions in real time. The system consists of current and voltage sensors, the Pzem- 004T sensor is used to measure the current and voltage of the heater. Node MCU ESP8266 processor is used for processing the measured data values from the sensors and transmit data to the NETPIE platform’s cloud storage and recording. Such information will be displayed on the NETPIE freeboard and notified via the LINE application according to the working status changes. From the experimental results shown that our proposed system can measure and display the data values correctly. It can accurately identify and abnormal operating conditions of the hot press machine perfectly. In addition the recorded and collected data values can be analyzed for more efficient maintenance planning.